Government Responsibility Post Covid-19 Pandemic with The Increase of Social Problems in Society - Suherman SH; Wicipto Setiadi; Iwan Erar Joesoef (Jurnal Penelitian Hukum De Jure, 2022)
The post-covid-19 pandemic in Indonesia has had a major social impact on society in the form of unemployment and divorce. The problem is whether the government can be held accountable for its policies in the context of overcoming the COVID-19 pandemic which has caused many social impacts on the society. The is study aimed to determine the government's responsibility for increasing social community such as increasing layoffs (PHK) and divorce in the society during the pandemic. The research methodology applied empirical methods. The results were based on the theory of government action, which is an action taken by state administrators in carrying out government duties that cause disputes between the people and the government. In Indonesia, the responsibilities of the government have not been regulated, and in practice, the society is still neglected. Society has surrendered to the consequences of the PPKM policy during the COVID-19 pandemic. Even if there are people who will file a civil lawsuit against the government. This lawsuit against government officials in the civil sector in Indonesia is based on the unlawful acts of the government as regulated in Article 1365 of the Civil Code.  The responsibilities of the Government other than in the field of civil law is in the field of state administrative law.